Есть ответ 👍

Решите выражения (c+2)(c-2)-4c(c-1) (x+8)^2-x(x+5) (x+4)(x+-1)^2 уравнение (x+2)(x-2)-x(x-6)=0 3x(4+-1)(6x+1)=11x (x+3)(x-+7)^2=0 (x+9)^2-x(x+8)=1

127
423
Посмотреть ответы 2

Ответы на вопрос:

zanna74
4,7(67 оценок)

1)-3с (в квадрате) 2)-х (в квадрате)-3х+16 3)х(в квадрате)+6х+18 4)2/3 5)1 6)1+2×корень из 6 1-2×корень из 6 7)-3+корень из 26 -3-корень из 26 4)х в квадрате-4-х в квадрате+6х=0 6х=4 х=2/3 5)12х+36х в квадрате-36х в квадрате+1=11х 12х-11х=1 х=1 6)х в квадрате-9-2х-14=0 х в квадрате-2х-23=0 д=4+92=96 х=(2+-√92)÷2=2÷2+-√96÷2=1+-2√6 7)2х+18-х в квадрате-8х=1 -х в квадрате-6х+17=0 д=36+68=104 х=(6+-√104)÷(-2)=6÷(-2)+-√104÷(-2)=-3+√26)
erekeshevadinar
4,4(74 оценок)

Отметим одз: корень х=-3 - не удовлетворяет одз ответ: 1/

Популярно: Алгебра